2023
DOI: 10.1177/08862605231174502
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Profile Analysis of Intimate Partner Violence Perpetrated by Men Seeking Help

Abstract: Past research has emphasized the need to identify profiles of men who perpetrate intimate partner violence (IPV) as a way to better understand this heterogeneous population and guide the development of tailored services. However, empirical validation for such profiles remains limited, since it still focuses on specific populations or fails to consider IPV as reported by men seeking treatment for IPV. We know little about the profiles of men who seek services for their use of IPV (with or without a justice refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Other works have found a similar profile of aggressors who exert violence more severely and frequently, while presenting antisocial personality disorder ( Capaldi and Clark, 1998 ; Andrews et al, 2000 ; Petersson et al, 2016 ) and borderline personality disorder ( Herrero et al, 2016 ). Furthermore, in another study it was observed that these men, in comparison to other groups, present psychological distress, attachment insecurity, childhood trauma and poor affect regulation more frequently, presenting the lowest levels of functioning ( Brassard et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other works have found a similar profile of aggressors who exert violence more severely and frequently, while presenting antisocial personality disorder ( Capaldi and Clark, 1998 ; Andrews et al, 2000 ; Petersson et al, 2016 ) and borderline personality disorder ( Herrero et al, 2016 ). Furthermore, in another study it was observed that these men, in comparison to other groups, present psychological distress, attachment insecurity, childhood trauma and poor affect regulation more frequently, presenting the lowest levels of functioning ( Brassard et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%